ANALISIS IDIOM BAHASA KOREA MENGGUNAKAN LEKSEM MATA - Budiarto, Maharani Tsani; Nurfitriana Ansas, Velayeti; Widyana, Ashanti (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the idiomatic meaning of the lexeme "eye" in Korean idioms and to explain the cultural values of Korea reflected within them. It employs a descriptive qualitative approach using content analysis methods. The data consists of 24 idioms containing the lexeme "eye," collected from various sources such as dictionaries, books, and official Korean language websites. The data analysis includes classifying the idioms based on their denotative and connotative meanings, as well as identifying the cultural elements they embody. The findings reveal that idioms with the lexeme "eye" possess diverse meanings, referring not only to visual function in a literal sense but also reflecting emotions, perception, judgment, and social relationships within Korean culture. In this study, the meanings of Korean idioms containing the lexeme "eye" reflect emotions and social dynamics more than just love although love remains an important theme. Cultural values such as social hierarchy, collectivism, and the importance of maintaining self-image are also reflected in these idioms. This study is expected to contribute to Korean language learning as a foreign language, particularly in mastering idioms that are rich in cultural significance.